Wish You Were Here? The Economic Impact of the Tourism Shutdown from Australia's 2019-20 `Black Summer' Bushfires - Vivienne Reiner; Navoda Liyana Pathirana; Ya-Yen Sun; Manfred Lenzen; Arunima Malik (Economics of Disasters and Climate Change, 2024)
Tourism, including education-related travel, is one of Australia's top exports and generates substantial economic stimulus from Australians travelling in their own country, attracting visitors to diverse areas including World Heritage rainforests, picturesque beachside villages, winery townships and endemic wildlife. The globally unprecedented 2019-20 bushfires burned worst in some of these pristine tourist areas. The fires resulted in tourism shutting down in many parts of the country over the peak tourist season leading up to Christmas and into the New Year, and tourism dropped in many areas not physically affected by the fires. Our research quantified the cost of the short-term shock from tourism losses across the entire supply chain using input-output (IO) analysis, which is the most common method for disaster analysis; to this end, we also developed a framework for disaggregating the direct fire damages in different tourism sectors from which to quantify the impacts, because after the fires, the economy was affected by COVID-19. We calculated losses of AU2.8~billion in total output, 1.56~billion in final demand, 810~million in income and 7300 jobs. Our estimates suggest aviation shouldered the most losses in both consumption and wages/salaries, but that accommodation suffered the most employment losses. The comprehensive analysis highlighted impacts throughout the nation, which could be used for budgeting and rebuilding in community-and-industry hotspots that may be far from the burn scar.
Keywords: C67; Z3; 330; Bushfires; Wildfires; Tourism; Input-output (IO) analysis; Economic impact